The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/suco.202100622
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of strengths of hybrid FR‐SCC by using deep‐learning and support vector regression models

Abstract: In this work, to estimate the compressive, splitting tensile, and flexural strength of self‐compacting concrete (SCC) having single fiber and binary, ternary, and quaternary fiber hybridization, the deep‐learning (DL) and support vector regression (SVR) models were devised. The fiber content and coarse aggregate/total aggregate ratio (CA/TA) were the variables for 24 designed mixtures. Four different fibers, which were a macro steel fiber, two types of micro steel fibers with different aspect ratio, and polyvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The study demonstrated that out of all the boosting algorithms employed, extreme gradient boosting algorithm proved to be the most accurate depicting the least absolute error of 1.43 MPa between real and predicted values. Similarly, Kina et al [ 56 ] utilized deep learning and SVM to estimate cs, fs, and split-tensile strength of SCC containing a mix of macro steel and micro synthetic fibres. The authors prepared 24 laboratory samples and measured their strength at 7, 28 and 90 days, then utilized that data to build ML models and concluded that deep learning predicted the SCC strength reinforced with different fibres more accurately than SVM.…”
Section: Relevant Literaturementioning
confidence: 99%
“…The study demonstrated that out of all the boosting algorithms employed, extreme gradient boosting algorithm proved to be the most accurate depicting the least absolute error of 1.43 MPa between real and predicted values. Similarly, Kina et al [ 56 ] utilized deep learning and SVM to estimate cs, fs, and split-tensile strength of SCC containing a mix of macro steel and micro synthetic fibres. The authors prepared 24 laboratory samples and measured their strength at 7, 28 and 90 days, then utilized that data to build ML models and concluded that deep learning predicted the SCC strength reinforced with different fibres more accurately than SVM.…”
Section: Relevant Literaturementioning
confidence: 99%
“… SVM, ANN, GEP 300 C–S 2021 Fly ash [ 37 ] 16. SVR, Deep Learning (DL) 24 C–S, Splitting tensile strength 2021 Fly ash, Silica fume [ 52 ] …”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the engineering properties of concrete in terms of brittle-ness, post-cracking capability and burst failure, short and randomly distributed fibers can be gradually added into concrete [2,3]. Adding fibers such as basalt, polypropylene (PP), glass, and steel fibers into cement-based composites is so common to upgrade the tensile performance and mechanical properties [4][5][6][7][8][9][10]. These advantageous properties of fibers cause an increase in the application of fiber-reinforced concrete throughout the world.…”
Section: Introductionmentioning
confidence: 99%